Senior food insecurity in the USA: a systematic literature review - Bertille Octavie Mavegam Tango Assoumou; Courtney Coughenour; Amruta Godbole; Ian McDonough (Cambridge University Press, 2023)
Abstract Objective: Understanding the factors associated with senior food insecurity is key to understanding senior-specific needs to develop targeted interventions and ultimately lower the prevalence and the incidence of food insecurity. We aimed to systematically review published literature and summarise the associated factors of food insecurity in older adults in the USA. Design: We searched PubMed, Scopus, Web of science, EconLit and JSTOR databases for peer-reviewed articles published in English between January 2005 and September 2019 that assessed food security or its associated factors for US adults aged 60 years and older. After a two-step screening process, twenty articles were retained and included in the review. Setting: NA Participants: NA Results: The majority of studies were cross-sectional (70 %), consisted of data from one state (60 %), and had large sample sizes. Food-insecure individuals were more likely to be younger, less educated, Black or African American, female, a current smoker, low income, and self-report fair/poor health, have chronic conditions, and utilise government assistance programmes. Food insecurity was associated with medication non-adherence, poor mental health outcomes and limitations in physical functioning. Results were mixed for overweight/obesity status. There was no discernable pattern related to the consistency of findings by the assessed quality of the included studies. Conclusions: Food insecurity is a prevalent and pervasive issue for older adults. The numerous correlates identified suggest that interventions aimed at enhancing food and nutrition safety net and medication assistance programmes are warranted, and upstream, systemic-level interventions may be best suited to deal with the correlates of food insecurity.